2015
DOI: 10.1589/jpts.27.273
|View full text |Cite
|
Sign up to set email alerts
|

Effect of horseback riding versus a dynamic and static horse riding simulator on sitting ability of children with cerebral palsy: a randomized controlled trial

Abstract: [Purpose] A randomized controlled trial was conducted to investigate the immediate effects of horseback riding (HR) and a dynamic (DHS) and static (SHS) horse riding simulator (OSIM uGallop, Taiwan) on sitting ability of children with cerebral palsy. [Subjects and Methods] Thirty children with cerebral palsy were recruited and randomly assigned into three groups. Children received 30 minutes of exercise according to their assigned group. The Segmental Assessment of Trunk Control (SATCo) and Gross Motor Functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
16

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 32 publications
1
44
0
16
Order By: Relevance
“…There are also several adjunctive interventions that when combined with task-specific motor training may augment the positive effects of training. These include electrical stimulation [65,[92][93][94], hydrotherapy [108,110,111], taping [159][160][161][162][163][164], transcranial direct current stimulation [101,[166][167][168], and virtual reality serious gaming [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] (yellow lights, weak positive). These interventions warrant more research as children reported finding gaming interventions rewarding and normalizing, and preferred electrical stimulation to wearing ankle-foot orthoses from a comfort perspective [93].…”
Section: Motor Interventionsmentioning
confidence: 99%
“…There are also several adjunctive interventions that when combined with task-specific motor training may augment the positive effects of training. These include electrical stimulation [65,[92][93][94], hydrotherapy [108,110,111], taping [159][160][161][162][163][164], transcranial direct current stimulation [101,[166][167][168], and virtual reality serious gaming [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] (yellow lights, weak positive). These interventions warrant more research as children reported finding gaming interventions rewarding and normalizing, and preferred electrical stimulation to wearing ankle-foot orthoses from a comfort perspective [93].…”
Section: Motor Interventionsmentioning
confidence: 99%
“…Dentre os estudos analisados, verificou-se que seis estudos foram publicados há menos de cinco anos (KWON et al, 2011(KWON et al, , 2015LEE;KIM;NA, 2014;PARK et al, 2014;TEMCHAROENSUK et al, 2015;ALEMDAROĞLU et al, 2016). Quanto ao local do estudo, quatro foram realizados nos Estados Unidos da América (BENDA; MCGIBBON; GR ANT, 2003;MCGIBBON et al, 2009;SHURTLEFF;ENGSBERG, 2010;SHURTLEFF;STANDEVEN;ENGSBERG, 2009), dois na Tailândia (CHERNG et al, 2004;TEMCHAROENSUK et al, 2015), um na Austrália (DAVIS et al, 2009), um na Turquia (ALEMDAROĞLU et al, 2016) e quatro na Coreia (KWON et al, 2011(KWON et al, , 2015LEE;KIM;NA, 2014;PARK et al, 2014). A amostra variou de 12 (SHURTLEFF; ENGSBERG, 2010) a 99 participantes (DAVIS et al, 2009 O instrumento predominantemente utilizado para avaliar a função motora foi a Gross Motor Function Measure (GMFM), presente em seis estudos (CHERNG et al, 2004;DAVIS et al, 2009;KWON et al, 2011KWON et al, , 2015PARK et al, 2014;TEMCHAROENSUK et al, 2015).…”
Section: Descrição Dos Estudosunclassified
“…Quanto ao local do estudo, quatro foram realizados nos Estados Unidos da América (BENDA; MCGIBBON; GR ANT, 2003;MCGIBBON et al, 2009;SHURTLEFF;ENGSBERG, 2010;SHURTLEFF;STANDEVEN;ENGSBERG, 2009), dois na Tailândia (CHERNG et al, 2004;TEMCHAROENSUK et al, 2015), um na Austrália (DAVIS et al, 2009), um na Turquia (ALEMDAROĞLU et al, 2016) e quatro na Coreia (KWON et al, 2011(KWON et al, , 2015LEE;KIM;NA, 2014;PARK et al, 2014). A amostra variou de 12 (SHURTLEFF; ENGSBERG, 2010) a 99 participantes (DAVIS et al, 2009 O instrumento predominantemente utilizado para avaliar a função motora foi a Gross Motor Function Measure (GMFM), presente em seis estudos (CHERNG et al, 2004;DAVIS et al, 2009;KWON et al, 2011KWON et al, , 2015PARK et al, 2014;TEMCHAROENSUK et al, 2015). Foi utilizada também a escala de equilíbrio pediátrica (Pediatric Balance Scale -PBS) (KWON et al, 2011, 2015; LEE; KIM; NA, 2014), a eletromiografia de superfície (BENDA; MCGIBBON; GRANT, 2003;MCGIBBON et al, 2009), a avaliação segmentar do controle de tronco (TEMCHAROENSUK et al, 2015), a avaliação cinemática (SHURTLEFF; ENGSBERG, 2010; SHURTLEFF; STANDEVEN; ENGSBERG, 2009), e a plataforma de equilíbrio (LEE; KIM; NA, 2014), entre outros.…”
Section: Descrição Dos Estudosunclassified
“…Previous research findings that significant improvement occurs in children with CP especially in postural control from sitting position when using the simulator on them [12]. Likewise, recent evidence suggests that horse riding simulator is one of the best ways to improve sitting and balance, and it recommends that dynamic horse riding simulator might be a successful surrogate in rehabilitation of cerebral palsy if real horses is unavailable [13]. Several studies reported that motor function, activities and muscle strength are significantly improved in children with C.P.…”
Section: Introductionmentioning
confidence: 99%